Rank Order of Small Molecule Induced Hypoxiamimesis to Prevent Retinopathy of Prematurity - Hoppe, George; Bolok, Youstina; McCollum, Leah; Zhang, Jin; Sears, Jonathan E. (Frontiers in Cell and Developmental Biology, 2020)
Here we rank order small molecule inhibitors of hypoxia inducible factor (HIF) prolyl hydroxylases (PHDs) using severity of oxygen induced retinopathy (OIR) as an outcome measure. Dose response analyses in cell cultures of hepatoma (Hep3B), retinal Müller cells (MIO-M1) and primary retinal endothelial cells were conducted to evaluate potency by comparing dose to HIF-1,2 protein levels by western blotting and in vivo the luciferase-transgene HIF reporter (luc-ODD). Each compound was placed in rank order by their ability to reduce neovascularization and capillary drop out in the OIR mouse model. An Epas1 KO confined to retinal Müller cells was used to determine whether successful protection by HIF stabilization requires HIF-2. Two candidate small molecules can prevent OIR by stabilizing HIF-1 to prevent oxygen induced growth attenuation and vascular obliteration. Müller cell HIF-2, the mediator of pathologic retinal angiogenesis, is not required for protection. The lack of dependence on Müller cell HIF-2 predicts that inhibition of HIF PHD will not drive pathological angiogenesis